DOES THE SOCIAL NETWORK RELATE WITH THE ENTREPRENEURSHIP? AN EMPIRICAL CONTENT ANALYSIS - Arissetyanto Nugroho; Janfry Sihite (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2015)
The aim of the content analysis is to construct social network terminology in entrepreneurship journal. There are 97 journal abstracts that analyzed from six keyword search query in Proquest, the queries are â€œEntrepreneur & Behaviorâ€, â€œEntrepreneurship & Creativity & Innovationâ€, â€œEntrepreneurship & Social Networkâ€, â€œEntrepreneurship & Cultureâ€, â€œEntrepreneurship & Marketingâ€ and â€œGlobal Entrepreneurship Monitorâ€. All the abstracts analyzed with Provalis Research QDA Miner, a Qualitative Quantitative Data Analysis software. QDA miner identified relevant keyword, relate keywords with jaggard coefficient of cooccurrence and the proximity plot. All the relevant keywords being analyzed with Multidimensional Scaling (MDS) and construct the relevant keywords regards to social network. Finally, there are two main findings, the first finding distinquishes the three level of analysis framework which are the individual level, the firm level and the macro level as representation of the continuous process to accumulateÂ resources. The second finding construct social network as national culture, furthermore the construct of social network closely related with social capital and human capital.Â Tujuan penelitian ini adalah untuk membangun konstruksi terminologi jejaring sosial berdasarkan jurnal kewirausahaan. Abstrak jurnal yang akan dianalisa diperoleh dengan kata kunci pencarian â€œEntrepreneur & Behaviorâ€, â€œEntrepreneurship & Creativity & Innovationâ€, â€œEntrepreneurship & Social Networkâ€, â€œEntrepreneurship & Cultureâ€, â€œEntrepreneurship & Marketingâ€ dan â€œGlobal Entrepreneurship Monitorâ€, total diperoleh 97 abstrak jurnal yang kemudian dianalisa dengan software analisa kualitatif kuantitatif Provalis Research. Kata kunci yang relevan diidentifikasi, selanjutnya coocurence dan proximity plot kata kunci dianalisa dengan koefisien jaccard. Didalam tahapan akhir semua kata kunci selanjutnya dianalisa dengan Multidimensional Scaling (MDS). MDS membangun konstruksi kata kunci yang berhubungan dengan jejaring sosial. 2 temuan utama didalam penelitian ini adalah: pertama, penelitian ini mendukung kerangka kerja analisa 3 tingkat kewirausahaan yaitu tingkat individual, perusahaan, dan makro sebagai kerangka kerja yang mencerminkan proses berkesinambungan kewirausahaan dalam akumulasi sumber daya. Temuan kedua membangun konstruksi bahwa jejaring sosial berkaitan erat dengan budaya nasional, modal sosial dan modal sumber daya manusia.Â